Tren fast fashion pakaian masa new normal di Indonesia: Efektivitas konsep sustainable fashion terhadap lingkungan - Ramadhan, Ahdiar Febri (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Globalization is one of the phenomena of the disappearance of national boundaries in the world. One that can be felt today is that clothing trends are one form of globalization. Conclusion: The fast fashion industry always provides and develops clothing production based on trends at very affordable prices in a short time. Since the Covid-19 pandemic occurred in 2020, the clothing industry, especially the fast fashion sector, has begun to rise by providing trends that adapt to the new normal lifestyle of consumers. Methods: This research was conducted descriptively qualitatively using a research approach where data was collected in the form of words, pictures, interview results, field notes, photos, videos, personal documents and other documentation. Findings: The purpose of this study is to determine the concept of fast fashion and its relationship to the global clothing industry and to determine the impact on the environment due to the development of the fast fashion industry and to explore designers in creating fashion towards sustainable fashion.